3D virtual worlds enriching innovation and collaboration in information systems research, development, and commercialisation - Dreher, Carl; Reiners, Torsten; Dreher, Naomi; Dreher, Heinz (Institute of Electrical and Electronics Engineers (IEEE) Industrial Electronic Society, 2009)
The increasing rate of technological development is changing how we interact socially, commercially, and politically, making this an exciting yet challenging time in which to live. As the pace of development is destabilising the status quo, it is increasingly important for individuals and organisations alike to adapt. Research, development, and commercialisation are important tools in facilitating innovation for organisations engaging in the modern knowledge/networked economy. As an emergent player in the networked economy, Digital Ecosystems have great potential for innovation. In particular 3D Virtual Worlds offer exciting opportunities for Information Systems research, development, and commercialisation. By their very structure, 3D Virtual Worlds such as Second Life provide a powerful context for innovation and collaboration: Second Life users are immersed in a 3D environment and empowered by a menu-based object-builder and a programming language; in-built text, voice, and body-language communication tools enrich communication, collaboration, and help provide a rich contextual presence. The community of users apply themselves to all realms of human endeavour, from recreational socialisation to systems development and entrepreneurial ventures. The current paper describes a university research commercialisation systems development project (of an Automated Essay Grading system called MarkIT), that utilises a 3D Digital Ecosystem for both promotion and implementation. Subsequently, this paper discusses the benefits, limitations, and suggestions for future innovation in research, development, and commercialisation of Information Systems incorporating 3D Virtual Worlds.